Biomolecule-assisted synthesis of In(OH)3 nanocubes and In2O3 nanoparticles: photocatalytic degradation of organic contaminants and CO oxidation. (6th November 2015) - Nayak, Arpan Kumar; Lee, Seungwon; Sohn, Youngku; Pradhan, Debabrata
Abstract: The synthesis of nanostructured materials without any hazardous organic chemicals and expensive capping reagents is one of the challenges in nanotechnology. Here we report on the L-arginine (a biomolecule)-assisted synthesis of single crystalline cubic In(OH)3 nanocubes of a size in the range of 30–60 nm along the diagonal using hydrothermal methods. Upon calcining at 750 °C for 1 h in air, In(OH)3 nanocubes are transformed into In2 O3 nanoparticles (NPs) with voids. The morphology transformation and formation of voids with the increase of the calcination temperature is studied in detail. The possible mechanism of the voids' formation is discussed on the basis of the Kirkendall effect. The photocatalytic properties of In(OH)3 nanocubes and In2 O3 NPs are studied for the degradation of rhodamin B and alizarin red S. Furthermore, the CO oxidation activity of In(OH)3 nanocubes and In2 O3 NPs is examined. The photocatalytic and CO oxidation activity are measured to be higher for In2 O3 NPs than for In(OH)3 nanocubes. This is attributed to the lower energy gap and higher specific surface area of the former. The present green synthesis has potential for the synthesis of other inorganic nanomaterials.